Cholinesterases, α-glycosidase, and carbonic anhydrase inhibition properties of 1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivatives: Synthetic analogues for the treatment of Alzheimer's disease and diabetes mellitus - Taslimi, Parham; Turhan, Kadir; Turkan, Fikret; Karaman, Halide Sedef; Turgut, Zuhal; Gulcin, Ilhami (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
In this study, using the Cu(OTf)(2) catalyst, 1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivative molecules were carried out in one step and with high yield (86-91%). The previously synthesized 1H-pyrazolo [1,2-b]phthalazine-5,10-dione derivatives, carbonic anhydrase I and II isozymes (hCA I and II), acetylcholinesterase (AChE), butyrylcholinesterase (BChE) and alpha-glycosidase (alpha-Gly) enzymes with K-i values in the range of 4.88-15.94 nM for hCA I, 7.04-20.83 nM for hCA II, 68.25-158.27 for AChE, 60.17-91.27 for BChE and 0.36-2.36 nM for alpha-Gly, respectively. In silico studies were performed on the molecules inhibiting hCA I, hCA II, AChE, BChE and alpha-Gly receptors. When we evaluated the data obtained in this work, we determined the inhibition type of the 1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivatives at the receptors. Reference inhibitors were used for all enzymes.
Keywords: 1H-pyrazolo[1, 2-b]phthalazine-5; 10-dione; Cholinesterase; Carbonic anhydrase; alpha-glycosidase; Molecular docking; GLUTATHIONE-S-TRANSFERASE; ACETYLCHOLINESTERASE; BUTYRYLCHOLINESTERASE; LACTOPEROXIDASE; ENZYME; ACHE; Biochemistry & Molecular Biology; Chemistry